(untitled) (The Pakistan Development Review, 2005)
Pakistan’s agriculture has grown rapidly since the 1960s, with an average annual growth of about 4 percent over the four decades till the end of the century. Agricultural growth at this rate was sustained by the technological progress embodied in the high-yielding varieties of grains and cotton, with supporting public investment in irrigation, agricultural research and extension (R&E), and physical infrastructure. This rate of agricultural growth has significantly contributed to the overall economic growth of about 6 percent per year during this period. Sustaining this performance presents a considerable challenge for the public policy framework for agriculture, not the least for the agricultural research and extension system in Pakistan. The central role of technological change in increasing agricultural productivity is well established in the wake of the Green Revolution experience across much of Asia. In the context of Pakistan, it has been estimated that almost 58 percent of the total output growth from 1960 to 1996 was due to technological change [Ali (2000)]. While improvements in the physical and market infrastructure, farmer education, price policies, and weather, all have their place in enhancing agricultural production, R&E investments has been regarded by far the most important contributor to agricultural productivity growth [Evenson and Rosegrant (1993); Byerlee (1994)].